Review article Education for transformation Four events on educational responses to neoliberalism and colonialism: World Education Forum, Palestine, October 2010 The Future of Higher Education in Scotland, Edinburgh February 2011 Educational Spaces for Alterity, Nottingham, April 2011 Beyond the Crisis: Learning from each other's struggles, Dublin, May 2011. (2011) - Scandrett, Eurig
No abstract available